New and Emerging Treatments for Lymphedema - Schaverien, Mark V.; Aldrich, Melissa B. (Seminars in Plastic Surgery, 2018)
Although nonoperative and operative treatments for lymphedema (LE) are well established, these procedures typically provide only partial relief from limb swelling, functional impairment, and the risk of cellulitis. The lack of a cure for LE, however, is due to an incomplete understanding of the underlying pathophysiological mechanisms, and current research efforts are focusing on elucidating these processes to provide new, targeted therapies for this prevalent disease for which there is no cure. This article reviews the current literature regarding the pathophysiological mechanisms that underlie LE, as well as new and emerging therapies for the condition.
Keywords: lymphedema; treatment; therapies; inflammation